PENGARUH KUALITAS PRODUK DAN CITRA MERK TERHADAP PEMBELIAN DAGING AYAM BROILER (Survei Terhadap Konsumen Daging Ayam Broiler di Kota Sukabumi Provinsi Jawa Barat) - Rifki Amrullah; Euis Dasipah; Karyana KS; Nendah Siti Permana; Tuti Gantini (Universitas Galuh, 2023)
This study aims to determine the effect of product quality and brand image on the purchase of broiler chicken meat.This research is a verification research using a survey method to consumers in Sukabumi City as the unit of analysis. The data collection technique used in this study was a questionnaire with a sample of 100 people. The analysis technique used is descriptive analysis and path analysis.The results of the partial study of product quality did not have a significant effect on the purchase of broiler chicken meat and brand image partially had a significant effect on the purchase of broiler chicken meat. Meanwhile, simultaneously product quality and brand image have a significant effect on the purchase of broiler chicken meat, with the level of influence can be seen from the hypothesis test, where the R square variable of 58.5% is influenced by this variable and 41.8% is influenced by other variables that are not explained. in this research.